THE GESTATION FOR INTERNATIONAL SUBSTITUTION AT FIVE YEARS OF THE "TOBIAS CASE" (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
Having passed five years since its resolution in 2012 by the Buenos Aires City Courts, I am intended to present some reflections on “Tobías’ case”, which took, at that time, public relevance as the “first co-parenting case” solved in our country.The intention of analyzing this case-law is based on two reasons mainly: in first place, to constitute, how was expressed the first case in our country which recognized the male co-parenting. In second place, as this case implies, for its biological imperative the recognition of the couple having resorted to gestational surrogacy, in relation to which our internal legal order remained, and so continues, silent about, constituting also one of the most opposed human assisted reproductive techniques.Being assumed that the practice was achieved outside from the Argentinean Republic, at India, it will attend the foreign elements that this case set out, and the National State recognition of its resulting filial positioning.Finally, some reflections will be made regarding the regulations of international private law included in the 2014/2015 Civil and Commercial Code, which may be applied to similar fact situations.
Keywords: gestational surrogacy; co- parenting; foreing elements